Influence of post‐synthesis NaCl flux treatment on the magnetic properties of jet‐milled SrFe12O19 powders. Issue 2 (29th September 2021) - Mocherla, Pavana S. V.; Ganesan, Priya; Prabhu, D.; Hebalkar, Neha Y.; Gopalan, R.; Varadaraju, U. V.
Abstract: A post‐synthesis NaCl flux treatment was carried out on jet‐milled strontium hexaferrite, SrFe12 O19 powders prepared by conventional high‐temperature solidstate reaction starting from SrCO3 and Fe2 O3 . Microstructural studies reveal that the adverse effects of jet‐milling on the particle morphology like jagged edges and ruptured surfaces have been effectively mitigated by annealing at elevated temperatures in the presence of molten NaCl flux. The coercivity values obtained from angle‐dependent M versus H measurements revealed that the coercivity mechanism in the jet‐milled powders is dominated by reverse nucleation due to the strain induced during milling. Annealing the powders in presence of NaCl flux changes the coercivity mechanism to exclusively domain rotation. This results in a dramatic increase of coercivity from 1.6 kOe for the jet‐milled powders to a maximum of 5.3 kOe for the flux‐annealed powders. XPS studies show that the NaCl flux treatment has not altered the chemical state of Fe.